Preparation method and application of lead-free ceramic material
BiFeO3-BaTiO3 ceramics were prepared by high-temperature solid phase method and doped ions were added, which solved the problems of high lead content and poor performance, and achieved the preparation of lead-free ceramic materials with high depolarization temperature, good piezoelectric properties and low dielectric loss.
Patent Information
- Application Number
- CN202411835533.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-13
- Publication Date
- 2025-04-18
- Estimated Expiration
- 2044-12-13
AI Technical Summary
Existing piezoelectric ceramic materials contain lead elements, which poses a threat to the environment and health. At the same time, BiFeO3-BaTiO3-based ceramics have oxygen vacancy and impurity phases during the preparation process, resulting in poor performance.
BiFeO3-BaTiO3 solid solution ceramics are prepared by high-temperature traditional solid-phase method, and doped ions such as Ga, Ca, Sr, Zr, Li2GeO3 and MnO2 are added to regulate the composition and microstructure of the ceramics, increase its depolarization temperature, electromechanical coupling coefficient and piezoelectric constant, and reduce dielectric loss.
Lead-free ceramic materials with high depolarization temperature, good piezoelectric properties and low dielectric loss are obtained, and the process is simple and low cost, which is suitable for large-scale production.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of piezoelectric ceramics, and in particular relates to a method for preparing a lead-free ceramic material. Background Art
[0002] Piezoelectric ceramics are electronic functional materials that can realize the mutual conversion of mechanical energy and electrical energy, and are widely used in the industrial field. Piezoelectric ceramics are widely used in aerospace, geological exploration, petrochemicals, automobile engines and other work. The current mainstream lead zirconate titanate piezoelectric ceramics (PZT-based piezoelectric ceramics) contain lead elements, which pose a serious threat to health and the environment. BiFeO3-based (BF) piezoelectric ceramics have a high depolarization temperature and good piezoelectric properties, but it is difficult to prepare pure BiFeO3. This is because the volatilization of bismuth oxide during high-temperature sintering causes oxygen vacancies, and the valence state of iron ions fluctuates, resulting in the presence of some impurity phases, resulting in large ceramic leakage current, low resistance, and poor electrical insulation, resulting in low breakdown field strength and poor ferroelectric properties. It is difficult to achieve the expected performance. BaTiO3 (BT) has high dielectric constant and low dielectric loss, and has good ferroelectric and piezoelectric potential. The introduction of BaTiO3 as the second phase to form a solid solution can inhibit the generation of impurities and stabilize the perovskite structure. However, due to the large difference in the firing temperature of BF and BT, the density of the ceramic is affected, resulting in large leakage current and high loss of BF-BT piezoelectric ceramics. Using ion doping to adjust the composition and microstructure is the mainstream means to form high-density BF-BT ceramics with good piezoelectric properties, but the presence of various components in piezoelectric ceramics often affects each other. How to obtain high-density, low-loss materials with good piezoelectric properties is still the focus of research. Summary of the invention
[0003] The present invention discloses a preparation method and application of a lead-free ceramic material. The lead-free ceramic material is prepared by a high-temperature conventional solid phase method and has a BiFeO3-BaTiO3 (BF-BT) solid solution structure. By adding doping ions to control the composition of the solid solution, a lead-free ceramic material with a high depolarization temperature, electromechanical coupling coefficient, piezoelectric constant and low dielectric loss is obtained. The lead-free piezoelectric ceramic material provided by the present invention has a simple synthesis process, low cost and can be mass-produced.
[0004] Specifically, the present invention discloses a method for preparing a lead-free ceramic material, the method comprising:
[0005] 1) Take Bi2O3, Fe2O3, BaCO3, TiO2, Ga2O3, CaCO3, SrCO3, ZrO2 as raw materials, according to (1-x)BiFe (1-m) Ga m O3-xBa (1-p-q) Ca p Srq Ti (1-n) Zr n O3 in a stoichiometric ratio, the mixture is placed in a ball mill, a dispersion medium and a ball milling medium are added, and the mixture is ball milled;
[0006] 2) Take out the evenly mixed slurry, dry it, compact it, place it in a heating furnace for pre-burning, cool it, and take it out;
[0007] 3) According to (1-x)BiFe (1-m) Ga m O3-xBa (1-p-q) Ca p Sr q Ti (1-n) Zr n O3: Li2GeO3: MnO2 = 100: a: b stoichiometric ratio, take GeO2, Li2CO3, MnO2 and mix with the product of step 2, put the mixture into a ball mill, add dispersion medium and ball milling medium, and ball mill to mix;
[0008] 4) Take out the uniformly mixed slurry, dry it, add a binder, and press it into a sheet to obtain a green body;
[0009] 5) Place the green body in a heating furnace for debinding, cool it, and take it out;
[0010] 6) The debinded ingredients are placed in a heating furnace for sintering and cooling to obtain lead-free ceramic materials.
[0011] Furthermore, (1-x)BiFe (1-m) Ga m O3-xBa (1-p-q) Ca p Sr q Ti (1-n) Zr n In O3, 0.32≤x≤0.34, 0.01≤m≤0.02, 0.006≤p=q≤0.012, n=p+q.
[0012] Furthermore, the pre-firing temperature is 750-850°C, the pre-firing time is 6-8h, and the heating rate is 3-5°C / min.
[0013] Further, in step 3), 0.16≤a≤0.20:0.5≤b≤0.8;.
[0014] Furthermore, in step 5), the process of the debinding treatment is to heat to 200-300°C and keep it for 1-3 hours, then heat to 500-600°C and keep it for 1-3 hours, and the heating rate is 3-5°C / min.
[0015] Furthermore, in step 6), the sintering temperature is 950-1050°C, the time is 4-6 h, and the heating rate is 3-5°C / min.
[0016] Furthermore, in step 1 and step 3, the ball milling time is 12-24 hours and the rotation speed is 200-400 r / min.
[0017] Furthermore, a lead-free ceramic material is prepared by the method described.
[0018] Furthermore, an application of the lead-free ceramic material is used in the fields of aerospace, geological exploration, petrochemical industry, automobile, electronic information technology or energy collection device.
[0019] Beneficial technical effects:
[0020] Compared with the prior art, the beneficial effects of the present invention are:
[0021] 1) The ceramic material of the present invention is based on BF-BT, and the raw materials do not contain lead. During the high-temperature sintering preparation process, no toxic and volatile metal lead compounds will be produced, and no environmental pollution will be caused, causing damage to health and ecology.
[0022] 2) The present invention utilizes Ga element to dope Fe sites, thereby reducing the oxygen vacancy concentration at Fe sites. At the same time, the co-doping of Ca, Sr, and Zr stabilizes the crystal structure of the material, which is conducive to grain boundary diffusion and migration, promotes grain growth, improves density, reduces leakage current, increases polarization voltage, and reduces dielectric loss;
[0023] 3) Adding Li2GeO3 and MnO2 to adjust the crystal phase composition and optimize the microstructure can increase the depolarization temperature, improve the piezoelectric performance, and increase the operating temperature range.
[0024] 4) The inventors found that when the molar ratio of Ca to Sr is 1:1, and the molar amount of Zr is equal to the sum of the molar amounts of Ca and Sr, the crystal structure is more stable, and the piezoelectric properties, depolarization temperature and electrical insulation of the lead-free ceramic material of the present invention are significantly better than those of ceramic materials doped by other means. DETAILED DESCRIPTION
[0025] The present invention is further described below in conjunction with specific embodiments. However, the protection scope of the present invention is not limited to the following embodiments, and any non-essential adjustments and modifications made to the present invention based on the above invention content still fall within the protection scope of the present invention.
[0026] Example 1
[0027] 1) Take analytically pure Bi2O3, Fe2O3, BaCO3, TiO2, Ga2O3, CaCO3, SrCO3, and ZrO2 as raw materials, and 0.99 Ga 0.01 O3-0.33Ba 0.988 Ca 0.006 Sr 0.006 Ti 0.988 Zr 0.012 The mixture was placed in a ball mill, ethanol was added as a dispersion medium, the solid-liquid ratio was 3:1, zirconium oxide balls were added as ball milling media, the ball-to-material ratio was 1:1, and the ball milling was carried out for 16 hours at a speed of 300 r / min.
[0028] 2) Take out the mixed slurry, dry it in a drying oven at 90°C, crush it, sieve it with 100 mesh, then put it in a crucible for compaction, and pre-calculate it in a heating furnace at a heating rate of 4°C / min, a pre-calcination temperature of 750°C, and a pre-calcination time of 8h. Cool it to room temperature, take it out, crush it, and sieve it with 100 mesh;
[0029] 3) According to 0.67BiFe 0.99 Ga 0.01 O3-0.33Ba 0.988 Ca 0.006 Sr 0.006 Ti 0.988 Zr 0.012 O3: Li2GeO3: MnO2 = 100: 0.16: 0.5 stoichiometric ratio, take GeO2, Li2CO3, MnO2 and mix with the product of step 2, put the mixture into a ball mill, add ethanol as a dispersion medium, the solid-liquid ratio is 3:1, add zirconium oxide balls as ball milling medium, the ball-to-material ratio is 1:1, ball milling for 16 hours, the rotation speed is 300r / min;
[0030] 4) Take out the mixed slurry, dry it in a drying oven at 90°C, crush it, sieve it through 100 mesh, then add 5wt% PVA, and press it into tablets at a pressure of 12 MPa to obtain a green body with a diameter of 10 mm and a thickness of 1.0 mm;
[0031] 5) Place the blank in a heating furnace at a heating rate of 4°C / min, heat to 200°C and keep warm for 3 hours, then heat to 500°C and keep warm for 3 hours, cool to room temperature and take out;
[0032] 6) The debinded ingredients are placed in a heating furnace for sintering at a heating rate of 4°C / min, a sintering temperature of 950°C, and a sintering time of 6 h. The mixture is cooled to room temperature to obtain a sample.
[0033] Example 2
[0034] 1) Take analytically pure Bi2O3, Fe2O3, BaCO3, TiO2, Ga2O3, CaCO3, SrCO3, and ZrO2 as raw materials, and 0.98 Ga 0.02 O3-0.33Ba 0.976 Ca 0.012 Sr 0.012 Ti 0.976 Zr 0.024 The mixture was placed in a ball mill, ethanol was added as a dispersion medium, the solid-liquid ratio was 3:1, zirconium oxide balls were added as ball milling media, the ball-to-material ratio was 1:1, and the ball milling was carried out for 16 hours at a speed of 300 r / min.
[0035] 2) Take out the mixed slurry, dry it in a drying oven at 90°C, crush it, sieve it with 100 mesh, then put it in a crucible for compaction, and pre-burn it in a heating furnace at a heating rate of 4°C / min, a pre-burning temperature of 800°C, and a pre-burning time of 7h. Cool it to room temperature, take it out, crush it, and sieve it;
[0036] 3) According to 0.67BiFe 0.98 Ga 0.02 O3-0.33Ba 0.976 Ca 0.012 Sr 0.012 Ti 0.976 Zr 0.024 The stoichiometric ratio of O3: Li2GeO3: MnO2 is 100: 0.20: 0.8. GeO2, Li2CO3, MnO2 are mixed with the product of step 2. The mixture is placed in a ball mill. Ethanol is added as a dispersion medium with a solid-liquid ratio of 3:5. Zirconia balls are added as ball milling media with a ball-to-material ratio of 1:1. The ball milling is performed for 16 hours at a rotation speed of 300 r / min.
[0037] 4) Take out the mixed slurry, dry it in a drying oven at 90°C, crush it, sieve it through 100 mesh, then add 5wt% PVA, and press it into tablets at a pressure of 12 MPa to obtain a green body with a diameter of 10 mm and a thickness of 1.0 mm;
[0038] 5) Place the blank in a heating furnace at a heating rate of 4°C / min, heat to 250°C and keep warm for 2 hours, then heat to 550°C and keep warm for 2 hours, cool to room temperature and take out;
[0039] 6) The debinded ingredients are placed in a heating furnace for sintering at a heating rate of 4°C / min, a sintering temperature of 1000°C, and a sintering time of 5 h. The mixture is cooled to room temperature to obtain a sample.
[0040] Example 3
[0041] 1) Take analytically pure Bi2O3, Fe2O3, BaCO3, TiO2, Ga2O3, CaCO3, SrCO3, and ZrO2 as raw materials, and 0.985 Ga 0.015 O3-0.33Ba 0.984 Ca 0.008 Sr 0.008 Ti 0.984 Zr 0.016 The mixture was placed in a ball mill, ethanol was added as a dispersion medium, the solid-liquid ratio was 3:1, zirconium oxide balls were added as ball milling media, the ball-to-material ratio was 1:1, and the ball milling was carried out for 16 hours at a speed of 300 r / min.
[0042] 2) Take out the mixed slurry, dry it in a drying oven at 90°C, crush it, sieve it with 100 mesh, then put it in a crucible for compaction, and pre-burn it in a heating furnace at a heating rate of 4°C / min, a pre-burning temperature of 850°C, and a pre-burning time of 6h. Cool it to room temperature, take it out, crush it, and sieve it;
[0043] 3) According to 0.67BiFe 0.985 Ga 0.015 O3-0.33Ba 0.984 Ca 0.008 Sr 0.008 Ti 0.984 Zr 0.016 The stoichiometric ratio of O3: Li2GeO3: MnO2 is 100: 0.18: 0.7. GeO2, Li2CO3, MnO2 are mixed with the product of step 2. The mixture is placed in a ball mill. Ethanol is added as a dispersion medium with a solid-liquid ratio of 3:1. Zirconia balls are added as ball milling media with a ball-to-material ratio of 1:1. The ball milling is performed for 16 hours at a speed of 300 r / min.
[0044] 4) Take out the mixed slurry, dry it in a drying oven at 90°C, crush it, sieve it through 100 mesh, then add 5wt% PVA, and press it into tablets at a pressure of 12 MPa to obtain a green body with a diameter of 10 mm and a thickness of 1.0 mm;
[0045] 5) Place the blank in a heating furnace at a heating rate of 4°C / min, heat to 300°C and keep warm for 1 hour, then heat to 600°C and keep warm for 1 hour, cool to room temperature and take out;
[0046] 6) The debinded ingredients are placed in a heating furnace for sintering at a heating rate of 4°C / min, a sintering temperature of 1050°C, and a sintering time of 4 h. The mixture is cooled to room temperature to obtain a sample.
[0047] Example 4
[0048] 1) Take analytically pure Bi2O3, Fe2O3, BaCO3, TiO2, Ga2O3, CaCO3, SrCO3, and ZrO2 as raw materials, and 0.985 Ga 0.015 O3-0.33Ba 0.98 Ca 0.01 Sr 0.01 Ti 0.98 Zr 0.02 The mixture was placed in a ball mill, ethanol was added as a dispersion medium, the solid-liquid ratio was 3:1, zirconium oxide balls were added as ball milling media, the ball-to-material ratio was 1:1, and the ball milling was carried out for 16 hours at a speed of 300 r / min.
[0049] 2) Take out the mixed slurry, dry it in a drying oven at 90°C, crush it, sieve it with 100 mesh, then put it in a crucible for compaction, and pre-burn it in a heating furnace at a heating rate of 4°C / min, a pre-burning temperature of 800°C, and a pre-burning time of 7h. Cool it to room temperature, take it out, crush it, and sieve it;
[0050] 3) According to 0.67BiFe 0.985 Ga 0.015 O3-0.33Ba 0.98 Ca 0.01 Sr 0.01 Ti 0.98 Zr 0.02 O3: Li2GeO3: MnO2 = 100: 0.18: 0.65 stoichiometric ratio, take GeO2, Li2CO3, MnO2 and mix with the product of step 2, put the mixture into a ball mill, add ethanol as a dispersion medium, the solid-liquid ratio is 3:1, add zirconium oxide balls as ball milling medium, the ball-to-material ratio is 1:1, ball milling for 16 hours, the rotation speed is 300r / min;
[0051] 4) Take out the mixed slurry, dry it in a drying oven at 90°C, crush it, sieve it through 100 mesh, then add 5wt% PVA, and press it into tablets at a pressure of 12 MPa to obtain a green body with a diameter of 10 mm and a thickness of 1.0 mm;
[0052] 5) Place the blank in a heating furnace at a heating rate of 4°C / min, heat to 250°C and keep warm for 2 hours, then heat to 550°C and keep warm for 2 hours, cool to room temperature and take out;
[0053] 6) The debinded ingredients are placed in a heating furnace for sintering at a heating rate of 4°C / min, a sintering temperature of 1000°C, and a sintering time of 5 h. The mixture is cooled to room temperature to obtain a sample.
[0054] Example 5
[0055] 1) Take analytically pure Bi2O3, Fe2O3, BaCO3, TiO2, Ga2O3, CaCO3, SrCO3, and ZrO2 as raw materials, and 0.985 Ga 0.015 O3-0.32Ba 0.98 Ca 0.01 Sr 0.01 Ti 0.98 Zr 0.02 The mixture was placed in a ball mill, ethanol was added as a dispersion medium, the solid-liquid ratio was 3:1, zirconium oxide balls were added as ball milling media, the ball-to-material ratio was 1:1, and the ball milling was carried out for 16 hours at a speed of 300 r / min.
[0056] 2) Take out the mixed slurry, dry it in a drying oven at 90°C, crush it, sieve it with 100 mesh, then put it in a crucible for compaction, and pre-burn it in a heating furnace at a heating rate of 4°C / min, a pre-burning temperature of 800°C, and a pre-burning time of 7h. Cool it to room temperature, take it out, crush it, and sieve it;
[0057] 3) According to 0.68BiFe 0.985 Ga 0.015 O3-0.32Ba 0.98 Ca 0.01 Sr 0.01 Ti 0.98 Zr 0.02 O3: Li2GeO3: MnO2 = 100: 0.18: 0.65 stoichiometric ratio, take GeO2, Li2CO3, MnO2 and mix with the product of step 2, put the mixture into a ball mill, add ethanol as a dispersion medium, the solid-liquid ratio is 3:1, add zirconium oxide balls as ball milling medium, the ball-to-material ratio is 1:1, ball milling for 16 hours, the rotation speed is 300r / min;
[0058] 4) Take out the mixed slurry, dry it in a drying oven at 90°C, crush it, sieve it through 100 mesh, then add 5wt% PVA, and press it into tablets at a pressure of 12 MPa to obtain a green body with a diameter of 10 mm and a thickness of 1.0 mm;
[0059] 5) Place the blank in a heating furnace at a heating rate of 4°C / min, heat to 250°C and keep warm for 2 hours, then heat to 550°C and keep warm for 2 hours, cool to room temperature and take out;
[0060] 6) The debinded ingredients are placed in a heating furnace for sintering at a heating rate of 4°C / min, a sintering temperature of 1000°C, and a sintering time of 5 h. The mixture is cooled to room temperature to obtain a sample.
[0061] Example 6
[0062] 1) Take analytically pure Bi2O3, Fe2O3, BaCO3, TiO2, Ga2O3, CaCO3, SrCO3, and ZrO2 as raw materials, and 0.985 Ga 0.015 O3-0.34Ba 0.98 Ca 0.01 Sr 0.01 Ti 0.98 Zr 0.02 The mixture was placed in a ball mill, ethanol was added as a dispersion medium, the solid-liquid ratio was 3:1, zirconium oxide balls were added as ball milling media, the ball-to-material ratio was 1:1, and the ball milling was carried out for 16 hours at a speed of 300 r / min.
[0063] 2) Take out the mixed slurry, dry it in a drying oven at 90°C, crush it, sieve it with 100 mesh, then put it in a crucible for compaction, and pre-burn it in a heating furnace at a heating rate of 4°C / min, a pre-burning temperature of 800°C, and a pre-burning time of 7h. Cool it to room temperature, take it out, crush it, and sieve it;
[0064] 3) According to 0.66BiFe 0.985 Ga 0.015 O3-0.34Ba 0.98 Ca 0.01 Sr 0.01 Ti 0.98 Zr 0.02 O3: Li2GeO3: MnO2 = 100: 0.18: 0.65 stoichiometric ratio, take GeO2, Li2CO3, MnO2 and mix with the product of step 2, put the mixture into a ball mill, add ethanol as a dispersion medium, the solid-liquid ratio is 3:1, add zirconium oxide balls as ball milling medium, the ball-to-material ratio is 1:1, ball milling for 16 hours, the rotation speed is 300r / min;
[0065] 4) Take out the mixed slurry, dry it in a drying oven at 90°C, crush it, sieve it through 100 mesh, then add 5wt% PVA, and press it into tablets at a pressure of 12 MPa to obtain a green body with a diameter of 10 mm and a thickness of 1.0 mm;
[0066] 5) Place the blank in a heating furnace at a heating rate of 4°C / min, heat to 250°C and keep warm for 2 hours, then heat to 550°C and keep warm for 2 hours, cool to room temperature and take out;
[0067] 6) The debinded ingredients are placed in a heating furnace for sintering at a heating rate of 4°C / min, a sintering temperature of 1000°C, and a sintering time of 5 h. The mixture is cooled to room temperature to obtain a sample.
[0068] Comparative Example 1
[0069] 1) Take analytically pure Bi2O3, Fe2O3, BaCO3, and TiO2 as raw materials, mix them according to the stoichiometric ratio of 0.67BiFeO3-0.33BaTiO3, put the mixture into a ball mill, add ethanol as the dispersion medium, the solid-liquid ratio is 3:1, add zirconia balls as the ball milling medium, the ball-to-material ratio is 1:1, and ball mill for 16 hours at a speed of 300r / min;
[0070] 2) Take out the mixed slurry, dry it in a drying oven at 90°C, crush it, sieve it with 100 mesh, then put it in a crucible for compaction, and pre-burn it in a heating furnace at a heating rate of 4°C / min, a pre-burning temperature of 800°C, and a pre-burning time of 7h. Cool it to room temperature, take it out, crush it, and sieve it;
[0071] 3) According to the stoichiometric ratio of 0.67BiFeO3-0.33BaTiO3:Li2GeO3:MnO2=100:0.18:0.65, GeO2, Li2CO3, MnO2 and the product of step 2 were mixed, the mixture was placed in a ball mill, ethanol was added as a dispersion medium, the solid-liquid ratio was 3:1, zirconia balls were added as ball milling media, the ball-to-material ratio was 1:1, and the ball milling was carried out for 16 hours at a speed of 300 r / min;
[0072] 4) Take out the mixed slurry, dry it in a drying oven at 90°C, crush it, sieve it through 100 mesh, then add 5wt% PVA, and press it into tablets at a pressure of 12 MPa to obtain a green body with a diameter of 10 mm and a thickness of 1.0 mm;
[0073] 5) Place the blank in a heating furnace at a heating rate of 4°C / min, heat to 250°C and keep warm for 2 hours, then heat to 550°C and keep warm for 2 hours, cool to room temperature and take out;
[0074] 6) The debinded ingredients are placed in a heating furnace for sintering at a heating rate of 4°C / min, a sintering temperature of 1000°C, and a sintering time of 5 h. The mixture is cooled to room temperature to obtain a sample.
[0075] Comparative Example 2
[0076] 1) Take analytically pure Bi2O3, Fe2O3, BaCO3, TiO2, CaCO3, SrCO3 as raw materials, according to 0.67BiFeO3-0.33Ba 0.98 Ca 0.01 Sr 0.01 TiO3 was mixed in a stoichiometric ratio, the mixture was placed in a ball mill, ethanol was added as a dispersion medium, the solid-liquid ratio was 3:1, zirconium oxide balls were added as ball milling media, the ball-to-material ratio was 1:1, and the ball milling was carried out for 16 hours at a speed of 300 r / min;
[0077] 2) Take out the mixed slurry, dry it in a drying oven at 90°C, crush it, sieve it with 100 mesh, then put it in a crucible for compaction, and pre-burn it in a heating furnace at a heating rate of 4°C / min, a pre-burning temperature of 800°C, and a pre-burning time of 7h. Cool it to room temperature, take it out, crush it, and sieve it;
[0078] 3) According to 0.67BiFeO3-0.33Ba 0.98 Ca 0.01 Sr 0.01 The stoichiometric ratio of TiO3: Li2GeO3: MnO2 is 100: 0.18: 0.65. GeO2, Li2CO3, MnO2 are mixed with the product of step 2. The mixture is placed in a ball mill. Ethanol is added as a dispersion medium with a solid-liquid ratio of 3:1. Zirconia balls are added as ball milling media with a ball-to-material ratio of 1:1. The ball milling is performed for 16 hours at a rotation speed of 300 r / min.
[0079] 4) Take out the mixed slurry, dry it in a drying oven at 90°C, crush it, sieve it through 100 mesh, then add 5wt% PVA, and press it into tablets at a pressure of 12 MPa to obtain a green body with a diameter of 10 mm and a thickness of 1.0 mm;
[0080] 5) Place the blank in a heating furnace at a heating rate of 4°C / min, heat to 250°C and keep warm for 2 hours, then heat to 550°C and keep warm for 2 hours, cool to room temperature and take out;
[0081] 6) The debinded ingredients are placed in a heating furnace for sintering at a heating rate of 4°C / min, a sintering temperature of 1000°C, and a sintering time of 5 h. The mixture is cooled to room temperature to obtain a sample.
[0082] Comparative Example 3
[0083] 1) Take analytically pure Bi2O3, Fe2O3, BaCO3, TiO2, Ga2O3, and ZrO2 as raw materials, and 0.985 Ga 0.015 O3-0.33Ba 0.98 Ti 0.98 Zr 0.02 The mixture was placed in a ball mill, ethanol was added as a dispersion medium, the solid-liquid ratio was 3:1, zirconium oxide balls were added as ball milling media, the ball-to-material ratio was 1:1, and the ball milling was carried out for 16 hours at a speed of 300 r / min.
[0084] 2) Take out the mixed slurry, dry it in a drying oven at 90°C, crush it, sieve it with 100 mesh, then put it in a crucible for compaction, and pre-burn it in a heating furnace at a heating rate of 4°C / min, a pre-burning temperature of 800°C, and a pre-burning time of 7h. Cool it to room temperature, take it out, crush it, and sieve it;
[0085] 3) According to 0.67BiFe 0.985 Ga 0.015 O3-0.33Ba 0.98 Ca 0.01 Sr 0.01 Ti 0.98 Zr 0.02 O3: Li2GeO3: MnO2 = 100: 0.18: 0.65 stoichiometric ratio, take GeO2, Li2CO3, MnO2 and mix with the product of step 2, put the mixture into a ball mill, add ethanol as a dispersion medium, the solid-liquid ratio is 3:1, add zirconium oxide balls as ball milling medium, the ball-to-material ratio is 1:1, ball milling for 16 hours, the rotation speed is 300r / min;
[0086] 4) Take out the mixed slurry, dry it in a drying oven at 90°C, crush it, sieve it through 100 mesh, then add 5wt% PVA, and press it into tablets at a pressure of 12 MPa to obtain a green body with a diameter of 10 mm and a thickness of 1.0 mm;
[0087] 5) Place the blank in a heating furnace at a heating rate of 4°C / min, heat to 250°C and keep warm for 2 hours, then heat to 550°C and keep warm for 2 hours, cool to room temperature and take out;
[0088] 6) The debinded ingredients are placed in a heating furnace for sintering at a heating rate of 4°C / min, a sintering temperature of 1000°C, and a sintering time of 5 h. The mixture is cooled to room temperature to obtain a sample.
[0089] Comparative Example 4
[0090] 1) Take analytically pure Bi2O3, Fe2O3, BaCO3, TiO2, Ga2O3, CaCO3, and ZrO2 as raw materials, and 0.985 Ga 0.015 O3-0.33Ba 0.98 Ca 0.02 Ti 0.98 Zr 0.02 The mixture was placed in a ball mill, ethanol was added as a dispersion medium, the solid-liquid ratio was 3:1, zirconium oxide balls were added as ball milling media, the ball-to-material ratio was 1:1, and the ball milling was carried out for 16 hours at a speed of 300 r / min.
[0091] 2) Take out the mixed slurry, dry it in a drying oven at 90°C, crush it, sieve it with 100 mesh, then put it in a crucible for compaction, and pre-burn it in a heating furnace at a heating rate of 4°C / min, a pre-burning temperature of 800°C, and a pre-burning time of 7h. Cool it to room temperature, take it out, crush it, and sieve it;
[0092] 3) According to 0.67BiFe 0.985 Ga 0.015 O3-0.33Ba 0.98 Ca 0.02 Ti 0.98 Zr 0.02 O3: Li2GeO3: MnO2 = 100: 0.18: 0.65 stoichiometric ratio, take GeO2, Li2CO3, MnO2 and mix with the product of step 2, put the mixture into a ball mill, add ethanol as a dispersion medium, the solid-liquid ratio is 3:1, add zirconium oxide balls as ball milling medium, the ball-to-material ratio is 1:1, ball milling for 16 hours, the rotation speed is 300r / min;
[0093] 4) Take out the mixed slurry, dry it in a drying oven at 90°C, crush it, sieve it through 100 mesh, then add 5wt% PVA, and press it into tablets at a pressure of 12 MPa to obtain a green body with a diameter of 10 mm and a thickness of 1.0 mm;
[0094] 5) Place the blank in a heating furnace at a heating rate of 4°C / min, heat to 250°C and keep warm for 2 hours, then heat to 550°C and keep warm for 2 hours, cool to room temperature and take out;
[0095] 6) The debinded ingredients are placed in a heating furnace for sintering at a heating rate of 4°C / min, a sintering temperature of 1000°C, and a sintering time of 5 h. The mixture is cooled to room temperature to obtain a sample.
[0096] Comparative Example 5
[0097] 1) Take analytically pure Bi2O3, Fe2O3, BaCO3, TiO2, Ga2O3, SrCO3, and ZrO2 as raw materials, and 0.985 Ga 0.015 O3-0.33Ba 0.98 Sr 0.02 Ti 0.98 Zr 0.02 The mixture was placed in a ball mill, ethanol was added as a dispersion medium, the solid-liquid ratio was 3:1, zirconium oxide balls were added as ball milling media, the ball-to-material ratio was 1:1, and the ball milling was carried out for 16 hours at a speed of 300 r / min.
[0098] 2) Take out the mixed slurry, dry it in a drying oven at 90°C, crush it, sieve it with 100 mesh, then put it in a crucible for compaction, and pre-burn it in a heating furnace at a heating rate of 4°C / min, a pre-burning temperature of 800°C, and a pre-burning time of 7h. Cool it to room temperature, take it out, crush it, and sieve it;
[0099] 3) According to 0.67BiFe 0.985 Ga 0.015O3-0.33Ba 0.98 Sr 0.02 Ti 0.98 Zr 0.02 O3: Li2GeO3: MnO2 = 100: 0.18: 0.65 stoichiometric ratio, take GeO2, Li2CO3, MnO2 and mix with the product of step 2, put the mixture into a ball mill, add ethanol as a dispersion medium, the solid-liquid ratio is 3:1, add zirconium oxide balls as ball milling medium, the ball-to-material ratio is 1:1, ball milling for 16 hours, the rotation speed is 300r / min;
[0100] 4) Take out the mixed slurry, dry it in a drying oven at 90°C, crush it, sieve it through 100 mesh, then add 5wt% PVA, and press it into tablets at a pressure of 12 MPa to obtain a green body with a diameter of 10 mm and a thickness of 1.0 mm;
[0101] 5) Place the blank in a heating furnace at a heating rate of 4°C / min, heat to 250°C and keep warm for 2 hours, then heat to 550°C and keep warm for 2 hours, cool to room temperature and take out;
[0102] 6) The debinded ingredients are placed in a heating furnace for sintering at a heating rate of 4°C / min, a sintering temperature of 1000°C, and a sintering time of 5 h. The mixture is cooled to room temperature to obtain a sample.
[0103] Comparative Example 6
[0104] 1) Take analytically pure Bi2O3, Fe2O3, BaCO3, TiO2, Ga2O3, CaCO3, SrCO3, and ZrO2 as raw materials, and 0.985 Ga 0.015 O3-0.33Ba 0.98 Ca 0.01 Sr 0.01 Ti 0.98 Zr 0.02 The mixture was placed in a ball mill, ethanol was added as a dispersion medium, the solid-liquid ratio was 3:1, zirconium oxide balls were added as ball milling media, the ball-to-material ratio was 1:1, and the ball milling was carried out for 16 hours at a speed of 300 r / min.
[0105] 2) Take out the mixed slurry, dry it in a drying oven at 90°C, crush it, sieve it with 100 mesh, then put it in a crucible for compaction, and pre-burn it in a heating furnace at a heating rate of 4°C / min, a pre-burning temperature of 800°C, and a pre-burning time of 7h. Cool it to room temperature, take it out, crush it, and sieve it;
[0106] 3) According to 0.67BiFe 0.985 Ga 0.015 O3-0.33Ba 0.98Ca 0.01 Sr 0.01 Ti 0.98 Zr 0.02 The stoichiometric ratio of O3:GeO2:MnO2=100:0.18:0.65, take GeO2, MnO2 and mix with the product of step 2, put the mixture into a ball mill, add ethanol as a dispersion medium, the solid-liquid ratio is 3:1, add zirconium oxide balls as ball milling medium, the ball-to-material ratio is 1:1, ball milling for 16 hours, the rotation speed is 300r / min;
[0107] 4) Take out the mixed slurry, dry it in a drying oven at 90°C, crush it, sieve it through 100 mesh, then add 5wt% PVA, and press it into tablets at a pressure of 12 MPa to obtain a green body with a diameter of 10 mm and a thickness of 1.0 mm;
[0108] 5) Place the blank in a heating furnace at a heating rate of 4°C / min, heat to 250°C and keep warm for 2 hours, then heat to 550°C and keep warm for 2 hours, cool to room temperature and take out;
[0109] 6) The debinded ingredients are placed in a heating furnace for sintering at a heating rate of 4°C / min, a sintering temperature of 1000°C, and a sintering time of 5 h. The mixture is cooled to room temperature to obtain a sample.
[0110] Comparative Example 7
[0111] Adjust the stoichiometric ratio of BF-BT in step 1) to 0.67BiFe 0.97 Ga 0.03 O3-0.33Ba 0.95 Ca 0.02 Sr 0.03 Ti 0.95 Zr 0.05 O3, the other steps are the same as those in Example 4.
[0112] Comparative Example 8
[0113] In step 3, BF-BT:Li2GeO3:MnO2=100:1:1 is adjusted, and the other steps are the same as those in Example 4.
[0114] Comparative Example 9
[0115] The doping element Ga2O3 is replaced by Ni2O3, the doping element CaCO3 is replaced by MgCO3, and the doping element ZrO2 is replaced by CeO2. The doping ratio and other steps are the same as those in Example 4.
[0116] Performance Testing
[0117] The upper and lower surfaces of the samples of the embodiments and comparative examples of the present invention were polished, and then silver paste was applied on the polished surface, placed in an oven at 110°C for 30 minutes, and then placed in a muffle furnace, and the temperature was raised to 500°C at a heating rate of 4°C / min. After being kept warm for 30 minutes, it was naturally cooled to room temperature, and polarized at a voltage of 4 kV / mm for 30 minutes in a silicone oil bath at 120°C to form a test sample. The performance of the test sample was tested using a high-temperature dielectric analyzer and a coupled spectrometer produced by Agilent. The test results are shown in the following table. Table 1 lists the piezoelectric performance test results of the piezoelectric ceramics prepared in the embodiments and comparative examples, including the piezoelectric constant d 33 , electromechanical coupling coefficient k p , depolarization temperature T c , depolarization temperature T d and room temperature dielectric loss tan δ at 1 kHz.
[0118] Table 1
[0119]
[0120] Results Data
[0121] It can be seen from the experimental data that the BF-BT-based lead-free ceramic material of the present invention has a higher piezoelectric constant, electromechanical coupling coefficient and depolarization temperature, as well as lower dielectric loss. The experimental data in the embodiments and comparative examples can illustrate that the various doping elements of the present invention work synergistically to jointly improve the stability of the crystal structure, and the piezoelectric properties, depolarization temperature, depolarization temperature and electrical insulation of the material of the present invention are significantly better than those of ceramic materials with other doping methods. Although the content of the present invention has been described in detail through the above preferred embodiments, it should be recognized that the above description should not be considered as a limitation of the present invention.
Claims
1. A method for preparing a lead-free ceramic material, characterized in that: The method comprises: 1) Take Bi2O3, Fe2O3, BaCO3, TiO2, Ga2O3, CaCO3, SrCO3, ZrO2 as raw materials, according to (1-x)BiFe (1-m) Ga m O3-xBa (1-p-q) Ca p Sr q Ti (1-n) Zr n O3 is mixed in a stoichiometric ratio, wherein 0.32≤x≤0.34, 0.01≤m≤0.02, 0.006≤p=q≤0.012, and n=p+q, the mixture is placed in a ball mill, a dispersion medium and a ball milling medium are added, and the mixture is ball milled and mixed; 2) Take out the evenly mixed slurry, dry it, compact it, place it in a heating furnace for pre-burning, cool it, and take it out; 3) According to (1-x)BiFe (1-m) Ga m O3-xBa (1-p-q) Ca p Sr q Ti (1-n) Zr n O3: Li2GeO3: MnO2 = 100: a: b stoichiometric ratio, GeO2, Li2CO3, MnO2 and the product of step 2 are mixed, wherein 0.16≤a≤0.20: 0.5≤b≤0.8, the mixture is placed in a ball mill, a dispersion medium and a ball milling medium are added, and the mixture is ball milled and mixed; 4) Taking out the uniformly mixed slurry, drying it, adding a binder, and pressing it into a tablet to obtain a green body; 5) Place the green body in a heating furnace for debinding, cool it, and take it out; 6) The debinded ingredients are placed in a heating furnace for sintering and cooling to obtain lead-free ceramic materials.
2. A method for preparing a lead-free ceramic material as claimed in claim 1, characterized in that: The pre-firing temperature is 750-850° C., the pre-firing time is 6-8 hours, and the heating speed is 3-5° C. / min.
3. A method for preparing a lead-free ceramic material as claimed in claim 1, characterized in that: In step 5), the process of the debinding treatment is to heat to 200-300°C and keep it for 1-3 hours, then heat to 500-600°C and keep it for 1-3 hours, with a heating rate of 3-5°C / min.
4. A method for preparing a lead-free ceramic material as claimed in claim 1, characterized in that: In the step 6), the sintering temperature is 950-1050°C, the sintering time is 4-6 h, and the heating rate is 3-5°C / min.
5. A method for preparing a lead-free ceramic material according to any one of claims 1 to 4, characterized in that: In the step 1) and step 3), the ball milling time is 12-24 hours and the rotation speed is 200-400 r / min.
6. A lead-free ceramic material, characterized in that: The material is prepared by the method according to any one of claims 1 to 5.
7. A use of the lead-free ceramic material as claimed in claim 6, characterized in that: The material is used in the fields of aerospace, geological exploration, petrochemical engineering, automobiles, electronic information technology or energy collection devices.
Citation Information
Patent Citations
Barium titanate based leadless piezoceramic material doped and modified by lithium-aluminum ion pair and preparing method thereof
CN103979955A
Barium titanate-based leadless piezoelectric ceramic and preparation method and application thereof
CN106699176A